A comparative study of external possession in Spanish and English - Dwyer, Nathan; Suárez-Palma, Imanol (Borealis – An International Journal of Hispanic Linguistics, 2026)
This paper compares external possession in Spanish and English. English typically uses internal possession to express inalienable relationships between a possessor and a body-part noun (BPN) (e.g., “James saw her arm”). However, like Spanish, it also permits external possession when the possessor appears as the verb’s internal argument and the BPN occurs in a locative PP (e.g., “Carlos hit him on the arm”; “Carlos lo golpeó en el brazo”). We argue that in both languages the possessor originates inside the DP containing the BPN and undergoes possessor raising to the specifier of the locative PP to receive case from the verb. A key difference emerges with instrumental PPs: Spanish allows external possession with external arguments (e.g., “James abrió la puerta con la/su mano”), whereas English does not (“James opened the door with *the/his hand”). Contra previous analyses, we show that instrumental PPs are adjuncts, blocking possessor raising. We attribute the cross-linguistic contrast to the availability of an implicit possessor in Spanish BPNs, modeled as PRO. This element is controlled by a local c-commanding antecedent, typically the external argument, yielding an inalienable interpretation. English lacks this option, requiring overt possessors and therefore favoring internal possession in such contexts.